SOIL HEALTH AND AGRICULTURAL PRODUCTIVITY: INTEGRATING CONSERVATION PRACTICES WITH MODERN CROP PRODUCTION TECHNIQUES - Ahmed, Rania; Ibrahim, Murtadha; Jamin, Fitriah Suryani (Techno Agriculturae Studium of Research, 2026)
Soil degradation and declining agricultural productivity pose critical challenges for sustainable food systems globally. Maintaining soil health while achieving high crop yields requires innovative approaches that integrate ecological conservation with modern agronomic techniques. The need to reconcile productivity with long-term soil functionality underpins this study. The research aims to evaluate the effects of combining conservation practices, including cover cropping, reduced tillage, and organic amendments, with modern crop production technologies such as precision fertilization and optimized irrigation, on soil health and crop performance. Emphasis is placed on identifying synergistic effects that enhance both ecological and agronomic outcomes. A quasi-experimental design was implemented across replicated plots representing diverse soil types. Soil chemical, physical, and biological indicators were monitored alongside crop yield, biomass accumulation, and tissue nutrient content. Statistical analyses, including ANOVA and multivariate regression, were conducted to quantify differences among management approaches. Results indicate that integrated management significantly improves soil organic matter, microbial biomass, and nutrient availability, while increasing crop yield and biomass relative to conventional or conservation-only systems. Synergistic interactions between ecological and technological interventions promote soil resilience and resource-use efficiency. The study concludes that integrating conservation practices with modern crop production offers a viable pathway toward sustainable intensification. Evidence-based recommendations support both productivity enhancement and long-term soil stewardship, providing guidance for researchers, farmers, and policymakers.